1, 3, 5‐Triazino Peptide Derivatives: Synthesis, Characterization, and Preliminary Antileishmanial Activity. (20th February 2018) - Khattab, Sherine N.; Khalil, Hosam H.; Bekhit, Adnan A.; Abd El‐Rahman, Mohamed M.; de la Torre, Beatriz G.; El‐Faham, Ayman; Albericio, Fernando
Abstract: A library of short di‐, tri‐, and tetra‐peptides with an s ‐triazine moiety at the N terminus and either an amide or ethyl ester C terminus was prepared in solution and on the solid phase. The two remaining positions of the s ‐triazine moiety were substituted with methoxy, morpholino, or piperidino groups. All the synthesized peptide derivatives were analyzed by HPLC and fully characterized by IR spectroscopy, 1 H and 13 C NMR spectroscopy, elemental analysis, and mass spectrometry (MALDI TOF/TOF). A preliminary study of the antileishmanial activity of the 1, 3, 5‐triazinyl peptide derivatives revealed that four dipeptide amide derivatives showed higher antipromastigote or antiamastigote activity than the reference standard drug miltefosine with no significance acute toxicity. Abstract : Running rings around trypanosomes : 1, 3, 5‐Triazino peptide derivatives were assessed for antileishmanial activity. Four dipeptide amide derivatives demonstrated better antipromastigote or antiamastigote activity than the reference standard drug miltefosine and showed no significant acute toxicity.